2000
DOI: 10.1111/j.0014-3820.2000.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Population Differentiation in Marbled Murrelets: Historical Versus Contemporary Processes

Abstract: .— Mechanisms of population differentiation in highly vagile species such as seabirds are poorly understood. Previous studies of marbled murrelets (Brachyramphus marmoratus; Charadriiformes: Alcidae) found significant population genetic structure, but could not determine whether this structure is due to historical vicariance (e.g., due to Pleistocene glaciers), isolation by distance, drift or selection in peripheral populations, or nesting habitat selection. To discriminate among these possibilities, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 46 publications
2
52
0
Order By: Relevance
“…Contemporary gene flow is suggested. Additional support for these two locations as refugia comes from other studies that have shown that one or both of these locations were refugia for other bird species (Holder et al, 1999;Congdon et al, 2000).…”
Section: Refugiamentioning
confidence: 76%
See 1 more Smart Citation
“…Contemporary gene flow is suggested. Additional support for these two locations as refugia comes from other studies that have shown that one or both of these locations were refugia for other bird species (Holder et al, 1999;Congdon et al, 2000).…”
Section: Refugiamentioning
confidence: 76%
“…There is evidence that at least one large glacial refugium was present in Beringia in the areas north of the ice in the Bering land bridge area and in present-day Alaska and Siberia (Pielou, 1991; Figure 1). Researchers studying the phylogeography (geographic distributions of genetic lineages; Avise, 2000) of two bird species, the rock ptarmigan (Lagopus mutus; Holder et al, 1999) and the marbled murrelet (Brachyramphus marmoratus; Congdon et al, 2000), have postulated that one or two previously unknown refugia were present in the Bering Sea region, likely in the Aleutian Islands. However, there is presently no geological or fossil evidence to corroborate these cryptic Bering Sea refugia.…”
Section: Introductionmentioning
confidence: 99%
“…Beerli 1999;Hedrick 1999), some of which may not hold for petrels (e.g. Congdon et al 2000). In contrast, molecular assignments using programs such as BAYESASS make few assumptions (reviewed in Manel et al 2005).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Defining such units relies upon a wide array of criteria and for migratory birds may include morphological or plumage characteristics, behavioral patterns quantified by banding or radio telemetry, or geographic separation of population segments during all or part of the annual cycle. Genetic markers are now widely used to quantify population divergence, identify or clarify management and taxonomic units, and offer insights into both historical and more contemporary processes involved in levels of divergence (e.g., Congdon et al 2000;Scribner et al 2003;Spruell et al 2003;Gay et al 2004). Yet for many migratory species, historical processes (e.g., Pleistocene ice movements) have substantially influenced gene flow and contemporary geographic distribution (Hewitt 2000), resulting in disparities between behavioral patterns, such as site fidelity or philopatry, and range-wide genetic characteristics.…”
Section: Introductionmentioning
confidence: 99%